Content analysis of euthanasia polls in Australia and New Zealand: words do matter. Issue 10 (18th October 2021) - Grove, Graham; Hughes, Ian; Lovell, Melanie; Best, Megan
Abstract: Background: There has been widespread public and political interest in Euthanasia and Physician‐Assisted Suicide (EPAS) in recent years. Polling in Australia and New Zealand has generally shown a majority of people support some form of legal EPAS; however, the level of support varies between polls. Aim: To explore whether public support for and opposition to EPAS as measured in historic Australian and New Zealand polls has been influenced by the wording of survey questions. Methods: Australian and New Zealand random‐sample post‐1995 EPAS poll questions asked of the general public were identified and subjected to content analysis. Individual phrases and words were considered in terms of their favourability towards or unfavourability against EPAS and each poll question was assigned a net favourability score. Variation of support for EPAS based on year, location and favourability of language was analysed by various statistical methods. Results: Mean public support for EPAS in Australia and New Zealand between 1995 and the present was 70.2% with support ranging between 47 and 85%. Support did not vary by location and has remained unchanged over time. However, support was positively associated with increasing levels of favourable wording, accounting for over 20% variation in mean support. Allusions to hopelessness had an especially strong effect on increasing support for EPAS. Conclusion: Use of emotive phrases and language is associated with influencing attitudes to EPAS in Australia and New Zealand. Therefore, caution should be exercised when interpreting public support for EPAS based on individual polls.